WINE TOURISM AS AN INCREASINGLY VALUABLE REVENUE STREAM OF A WINERYS BUSINESS MODEL - Remeňová, Katarína; Skorková, Zuzana; Jankelová, Nadežda (Economics of Agriculture, 2019)
Nowadays, wine tourism belongs to the key business activities of a winery. It represents a diversification tool of a typical production company. The research paper aims to explore the relationship between wine tourism and business model parameters according to financial and production performance of a winery. The results of the parametric Independent sample t –test reveal that there is no difference in revenue, profit or gross margin between two groups of wineries with or without wine tourism activities. But the analysis gave proof about the difference in a number of revenue streams, key, and additional business activities. The effect size r for t- test was also calculated. Measuring the association between key performance indicators and wine tourism activities reveals the dependency with the number of revenue streams of a winery. Additional business activities are the most relevant parameter to perform better results in wine tourism.